Mental image role in the relationship analyzing between the provision and safety customers service and between social responsibility and the viewpoint of government and private bank customers in Al- Muthanna Governorate - Jahel, Shahad Baqer (International Journal of Psychosocial Rehabilitation, 2020)
In order to identify the role that the perceived mental image plays among customers of government banks operating in Al-Muthanna Governorate, in analyzing the relationship between service provision and safety as an independent variable, and between social responsibility as an approved variable for those banks. The Exploratory Factor Analysis (EFA) and Descriptive Statistics (DS) were adopted in addition,ANOVA, Pearson Correlation, and Linear Regression, to test research hypotheses, and for analyzing the questionnaire form that was distributed to 220 customers of Al-Rafidain and Al-Rasheed Banks, the Iraqi Islamic Bank and the Bank of Baghdad, accreditation of the program SPSSV.24, on the main premise that(The perceived mental image of customers influences the analysis of the relationship between the provision and safety of service and the social responsibility of governmental and private banks), the study reached a main conclusion, indicates that there was a strong correlation between the level of service safety and its method and social responsibility, this connection increases when that relationship mediates the customer's perceived mental image, on the level of services of those banks and their safety, and the extent of achieving social responsibility standards by those banks